Does self-paced exercise depend on executive processing? A narrative review of the current evidence. Issue 1 (1st January 2021) - Holgado, Darías; Sanabria, Daniel
ABSTRACT: Self-paced exercise is any physical activity in which the effort has to be distributed over time in order to achieve the objective of the event. Hence, self-paced aerobic exercise is a goal-directed behavior towards an objective that involves several cognitive processes. The aim of the present review is to ask the extent to which self-paced exercise might rely on executive functions and the empirical evidence of top-down processing on self-paced exercise. We discuss the evidence from different experimental manipulations showing a potential link between self-paced exercise and executive processing. We finally highlight some gaps in the literature and possible factors that might mediate the role of executive processing and self-paced exercise. Self-paced exercise is likely to be a highly complex process, in which a multitude of factors non-related to executive functions can also contribute to the ultimate decision to upregulate or downregulate exercise intensity.